Effects of Dioscorea esculenta and Eubacterium rectale on insulin receptor substrate 1 (Irs1) Expression in skeletal muscle and homeostatic model assessment-insulin resistance (HOMA-IR) in diabetic rats - . Sunarti; Tri Setyawati; Neni Oktiyani; Rio Jati Kusuma (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2015)
Low expression of insulin receptor substrate 1 (Irs1) is associated with insulin resistance and type 2 diabetes mellitus (type 2 DM). This study was performed to evaluate the effects of Dioscorea esculenta and Eubacterium rectale on the Irs1 expression in the skeletal muscle and the homeostatic model assessment-insulin resistance (HOMA-IR) of diabetic rats. Twenty-five male Wistar rats were divided into five groups i.e. non diabetic rats Group 1; diabetic rats as Group 2; diabetic rats + D. esculenta as Group 3; diabetic rats + E.rectale as Group 4 and diabetic rats + both E. rectale and D. esculenta as Group 5. Rats were made diabetic with induction of intraperitoneally injection of nicotinamide and streptozotocin. After four weeks of the interventions, the blood and skeletal muscles were taken. The Irs1 expression was analyzed with immunohistochemical staining, plasma glucose levels was analyzed using a spectrophotometer, and insulin was analyzed using ELISA methods. All intervention groups reduced plasma glucose levels and HOMA-IRs (p<0.001) and increased Irs1 expression. The greatest reduction of plasma glucose levels and increase of Irs1 expression in the skeletal muscle were found in Group 4, however, the lowest of HOMA-IR was seen in Group 5. These results suggested that D.esculenta, E.rectale, and the combination reduced plasma glucose levels and HOMA-IR by increasing Irs1 expression in skeletal muscle.